IMPLEMENTASI PERLINDUNGAN DAN PENGELOLAAN EKOSISTEM GAMBUT SERTA PENGENDALIAN KEBAKARAN HUTAN DAN LAHAN - Febr Yuliani (Universitas Riau, 2018)
Implementation of Protect and Ecosystem Management and Fire Control of Forest andField. Land and forest fires occurring every year in Riau Province until 2016 reaches 3,218 hectareswith the highest number of fires in Rokan Hilir Regency with 32 points. Other fire spots are alsospread in Pelalawan, Meranti, Rokan Hulu, Bengkalis, Inhil, and Inhu districts. Meanwhile, forestfires and peatlands in the eastern coastal region also continue. Until now, it was recorded that310.25 hectares of peatland had been burned in Meranti Regency. This research aims to find outthe Implementation of Protection and Management of Peat Ecosystem and Forest and Land FireControl in Meranti District, Riau Province. The type of this research is qualitative with explorativemethod. In Implementation of Protection and Management of Peatland Ecosystem and Forestand Land Fire Control in Meranti District has been done This can be seen from the managementindicators used in analyzing the Implementation of Peatland Protection and Management andForest and Land Fire Control in Meranti District. Evident with the occurrence of decrease of firespots in some villages even in 2016 not found the hotspots. In addition, Meranti District is alsoan international laboratory for the management of peat ecosystems. Efforts to protect and managepeatlands are back in order to return to their function.